CASE REPORT OF ANGELMAN SYNDROME- A CHILD WITH PATHOGENIC VARIANT c.678dup, p.(Leu227iLefster4) IN THE EXON 7 OF UBEZA GENE - Nonkulovski, Danilo; Sofijanova, Aspazija; Bojadzieva, Sonja; Kirovski, Ilija; Jordanova, Olivera Viktor (Journal of Morphological Sciences; Vol 6 No 3 (2023): JMS, 2023)
Angelman syndrome is rare and belongs to the group of genetic imprinting disorders where pathogenic mutations in the active gene are responsible for the disease, while pathogenic mutations in the inactive gene do not cause the disease. It's usually caused by problems with a gene located on chromosome 15 called the ubiquitin protein ligase E3A (UBE3A) gene. Some of pediatric patient don't have a family history of the disease. We present to you a 2 and a half year old female child with seizures which are difficult to control and recur in clusters, alternating with periods without attacks. Due to suspicion of epilepsy sent for genetic diagnosis. The presence of a pathogenic variant c.678dup, p.(Leu227iLefster4) in the in exon 7 of UBEZA gene in heterozygous form was proven. There is a change in the reading frame (frameshift), i.e. replacement of the amino acid leucine at position 227 with the amino acid isoleucine and termination of the protein after 4 amino acids. This variant has not been published in the literature so far. Family studies showed that the c678dup variant in the UBEZA gene was not present in the child's parents.  Additional analysis confirmed the biological connection of the parents with the child. These findings confirm that the pathogenic c678dup variant in the child arose de novo. Anticonvulsant therapy was prescribed and ketonic diet. Early diagnosis of Angelman syndrome and appropriate therapy enables a better quality of life for children. Keywords: Angelman syndrome, epilepsy, seizures, UBE3A gene